Fulminant Delta COVID-19 myocarditis: a case report of fatal primary cardiac dysfunction. Issue 4 (13th April 2022) - Thomson, Alistair; Totaro, Richard; Cooper, Wendy; Dennis, Mark
Abstract: Background: Whilst myocarditis or myocardial injury due to severe acute respiratory syndrome coronavirus 2 infection is commonly reported, profound primary cardiac dysfunction requiring mechanical circulatory support, with the development of fulminant myocarditis prior to respiratory failure, is rarely described. The endomyocardial biopsy (EMB) findings in these patients is seldom reported, the findings are varied, and effective treatment unknown. Case summary: A 39-year-old female with no significant past medical history and confirmed Delta variant coronavirus disease 2019 (COVID-19) infection (Day 3), presented with a 1 day history of diarrhoea, vomiting, and abdominal pain. The patient denied respiratory symptoms and chest X-ray was clear. Lactate level was 6.3, initial troponin T 118 ng/L. Despite resuscitation, the patient significantly deteriorated in the emergency department, resulting in pulseless electrical activity arrest requiring veno-arterial extra-corporeal membrane oxygenation cardiopulmonary resuscitation. Over the following 36 h, cardiac function deteriorated to near-complete left ventricular (LV) standstill. Coronary angiography revealed normal coronary arteries with slow flow. Endomyocardial biopsy showed diffuse interstitial macrophage infiltrate and small vessel thromboses. Left ventricular function did not improve over the following 7 days, and despite treatment with tocilizumab, high-dose steroids, and intravenous immunoglobulin, she eventually died due to disease-related complications. Discussion: Primary cardiac dysfunction secondary to COVID-19 infection is rarely reported. Little is known about the incidence, natural history, and pathophysiology of fulminant COVID-19 myocarditis. We present the most severe case of cardiac dysfunction due to COVID-19 reported in a young patient without respiratory compromise who never recovered from any cardiac function.